Perkembangan LKPD Berbasis Kearifan Lokal pada Materi-Materi Bencana Alam untuk Siswa SD Kelas I - Laila Fatmawati; Pristiya Irawati; Dholina Inang Pambudi; Purwadi; Budi Santoso (UM Purwokerto Press, 2021)
Student worksheets/Lembar Kerja Peserta Didik (LKPD) that promote local wisdom are still rarely found in elementary schools. Therefore, it is necessary to develop LKPD that supports the delivery of materials for the local wisdom preservation. This research aims to develop the LKPD based on local wisdom of natural disaster material for 1st grade elementary school students. The type of this research is Research and Development (RnD). The development procedure adopts the ADDIE model. The subject was the 1st Grade students at Unggulan Aisyiyah Elementary School in Bantul. However, due to the coronavirus pandemic, the research was only conducted until the validation test stage by expert lecturers. The data retrieval techniques were observations and interviews. The data was analyzed using qualitative and quantitative analysis. The criteria for the successful creation of LKPD can be seen from the assessment of validation experts. The results of the assessment by media experts are 77